x-2-x(x-2)=0 详细过程,并说明理由!
4x(2x+1)=3(2x+1) 详细过程,并说明理由!
急!急!急!
x-2-x(x-2)=0 详细过程,并说明理由!
4x(2x+1)=3(2x+1) 详细过程,并说明理由!
急!急!急!
(1).x-2-x(x-2)=0
即(x-2)-x(x-2)=0
即1*(x-2)-x(x-2)=0
即(1-x)(x-2)=0
(2).4x(2x+1)=3(2x+1)
4x(2x+1)-3(2x+1) =0
(4x-3)(2x+1)=0
x-2-x(x-2)=0
(x-2)-x(x-2)=0
(1-x)(x-2)=0 提公因式(x-2)
4x(2x+1)=3(2x+1)
4(2x+1) -3(2x+1) =0
(4-3)(2x+1) =0
2x+1=0 提公因式(2x-1)
(x-2)(1-x)=0,x=2或1
(2x+1)(4x-3)=0,x=-1/2或3/4
x-2-x(x-2)=0 提取(X-2)得(X-2)(1-X)=0得x=2或x=1
4x(2x+1)=3(2x+1)移项得4x(2x+1)-3(2x+1)0提取(2x+1)得(2x+1)(4-3)=0得x=0.5
一定要采纳哦、、、
第一题
(x-2)(1-x)=0
第二题
4x(2x+1)-3(2x+1) =0
(2x+1)(4x-3)=0